The 33 strategies of war - Greene, Robert (Penguin Books, 2006)
In The 33 Strategies of War, Greene has crafted an important addition to this ruthless and unique series. Spanning world civilizations, synthesizing dozens of political, philosophical, and religious texts and thousands of years of violent conflict, The 33 Strategies of War is a comprehensive guide to the subtle social game of everyday life informed by the most ingenious and effective military principles in war. Structured in Greene's trademark style, The 33 Strategies of War is the I-Ching of conflict, the contemporary companion to Sun Tzu's The Art of War. Abundantly illustrated with examples from history, including the folly and genius of everyone from Napoleon to Margaret Thatcher, Shaka the Zulu to Lord Nelson, Hannibal to Ulysses S. Grant, as well as movie moguls, Samurai swordsmen, and diplomats, each of the thirty-three chapters outlines a strategy that will help you win life's wars. Learn the offensive strategies that require you to maintain the initiative and negotiate from a position of strength, or the defensive strategies designed to help you respond to dangerous situations and avoid unwinnable wars. The great warriors of battlefields and drawing rooms alike demonstrate prudence, agility, balance, and calm, and a keen understanding that the rational, resourceful, and intuitive always defeat the panicked, the uncreative, and the stupid. An indispensable book, The 33 Strategies of War provides all the psychological ammunition you need to overcome patterns of failure and forever gain the upper hand.